RoSaVR : immersive VR Apps for road safety for kids - Raman, Aras (2016)
The term “Virtual Reality” is very widespread nowadays. It is because of the development in technology especially the smart phone technology and the computer technology. Back then, developing virtual reality system takes a lot of time and money and that includes many men power in the development process. Nowadays, the virtual reality technology becomes chip in the term of hardware and the software in development process, because of that many people try to develop virtual reality in many aspect. For example, the training simulation for pilots, treatment for person that has phobia in darkness or animals such as spider, dogs and cats. Moreover, virtual reality also becomes more popular in computer games technology, which was installed into their smart phone. They can get into the game only by using the smart phone that was placed into the Google. So based on the technology that we have today, this project is using virtual reality technology in learning process for the children to learn about road safety and help them to increase their understanding in that matter. The laws from the book are applied into this project to make a change from reading to immersion to the situation of every road law. So this project can increase children’s understanding on road safety rather than only reading the book. Lastly, the biggest hope that this project can help and achieve the objectives of this project.